180k views
4 votes
X + 2Let g(x) = x2 + 2 and h(x) =5Evaluate (hog)(x).(h o g)(x) =(Simplify your answer.)

X + 2Let g(x) = x2 + 2 and h(x) =5Evaluate (hog)(x).(h o g)(x) =(Simplify your answer-example-1

1 Answer

3 votes

If we have two funcions, f(x) and g(x), fog is f(g(x)). In other words, we substitute the x in the first function for g(x).

In your question:


\begin{gathered} g(x)=x^2+2 \\ h(x)=(x+2)/(5) \end{gathered}

hog(x) = h(g(x))


\begin{gathered} h(x)=(x+2)/(5) \\ hog(x)=h(g(x))=(g(x)+2)/(5) \\ hog(x)=((x^2+2)+2)/(5) \\ hog(x)=(x^2+4)/(5) \\ \end{gathered}

User Brad Koch
by
4.4k points